Dong fang shou xin : Ying ji Hua ren Zhao Tailai xian sheng juan zeng tong cao shui cai hua - Cheng, Cunjie, 1966- (Beijing : Wen wu chu ban she, 2014)
Summary in vernacular field only.
Keywords: China trade watercolor painting -- China -- Guangzhou -- Catalogs; Watercolor painting, Chinese -- China -- Guangzhou -- Ming-Qing dynasties, 1368-1912 -- Catalogs